2006
DOI: 10.1097/01.tp.0000244347.61060.af
|View full text |Cite
|
Sign up to set email alerts
|

Islet Isolation and Transplantation Outcomes of Pancreas Preserved with University of Wisconsin Solution Versus Two-Layer Method Using Preoxygenated Perfluorocarbon

Abstract: No beneficial effect of TLM on islet isolation and transplantation outcomes was observed. Our findings bring into question the true merit of routine use of TLM prior to islet isolation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 48 publications
(32 reference statements)
2
80
1
Order By: Relevance
“…In contrast to previous experiments that were performed in relatively small numbers of pancreases, these studies clearly revealed that pancreas storage in precharged PFD is unsufficient to increase islet yield, insulin secretory capacity and posttransplant function in recipients when compared to organ storage in UWS (Kin et al, 2006a, Caballero-Corbalan et al, 2007. Several reasons can be discussed for this observation.…”
Section: Pancreas Oxygenation For Subsequent Islet Transplantationcontrasting
confidence: 50%
See 1 more Smart Citation
“…In contrast to previous experiments that were performed in relatively small numbers of pancreases, these studies clearly revealed that pancreas storage in precharged PFD is unsufficient to increase islet yield, insulin secretory capacity and posttransplant function in recipients when compared to organ storage in UWS (Kin et al, 2006a, Caballero-Corbalan et al, 2007. Several reasons can be discussed for this observation.…”
Section: Pancreas Oxygenation For Subsequent Islet Transplantationcontrasting
confidence: 50%
“…As reported, this was the case for the studies from the Edmonton group (Tsujimura et al, 2002a, Tsujimura et al, 2004a, Salehi et al, 2006, Kin et al, 2006a but not for the study from the Nordic Network (Caballero-Corbalan et al, 2007). This is of particular relevance when pancreases from obese donors are recovered.…”
Section: Pancreas Oxygenation For Subsequent Islet Transplantationmentioning
confidence: 58%
“…In a rodent model, the TLM had a 100% success rate after 6 hours of cold preservation as compared with 50% after UW preservation (21). Two recent papers (22,23) reached different results in terms of the beneficial effect of TLM on human islet isola- presence of PFC in the solution. Our study is limited by the fact that the results are based primarily on in vitro cellular function after 48 hours of culture.…”
Section: Discussionmentioning
confidence: 99%
“…However, two recent largescale studies showed no beneficial effect of TLM, compared with UW storage, on human islet isolation and transplantation [21,22] . We reevaluated the effect of TLM using three different groups: group 1: UW simple storage; group 2: TLM performed by multiorgan procurement teams (not specialists in islet isolation); and group 3: TLM performed by specialists in islet isolation.…”
Section: Ervationmentioning
confidence: 99%